A prime-boost combination of a three-protein cocktail and multiepitopic MVA as a vaccine against Babesia bigemina elicits neutralizing antibodies and a Th1 cellular immune response in mice - Montenegro, Valeria Noely (2022)
In the intraerythrocytic protozoan parasites of the genus Babesia both innate and adaptive immune responses are necessary to confer protection against clinical disease. In particular, the adaptive immune response involves the production of neutralizing antibodies as well as the presentation of parasite antigens to CD4+ T lymphocytes by professional antigen-presenting cells. Therefore, the development of alternative vaccines that replace the use of live attenuated strains should include relevant epitopes targeting both B and T cell responses. The aim of this study was to design new Babesia bigemina immunogens and evaluate the humoral and cellular responses in mice. To achieve this, three B. bigemina recombinant antigens called Apical Membrane Antigen 1 (AMA-1), Rhoptry Associated Protein 1 (RAP-1) and the Thrombospondin Related Anonymous Protein 1 (TRAP-1) were obtained. Besides, two recombinant modified vaccinia virus Ankara vectors coding for chimeric constructs containing bioinformatically predicted B and T cell epitopes from the same three antigens were generated. These immunogens were evaluated in prime-boost heterologous schemes. Among the combinations tested, priming with a cocktail of the three proteins followed by a booster immunization with a mix of both viruses induced the highest activation of IFN-γ+ CD4+ and CD8+ antigen-specific T cell responses. Remarkably, all vaccine schemes containing antigen cocktails also induced antibodies that were capable of neutralizing merozoite invasion of bovine erythrocytes in vitro at a level comparable to an anti B. bigemina hyperimmune bovine serum. Our results offer a new perspective for vaccines against B. bigemina combining bioinformatics predictions and prime-boost immunization regimes for future control measures against bovine babesiosis.